Sarana Sehat Kalijudan (SARASEHAN) Whatsapp Group: A Platform to Disseminate Children's Dental and Oral Health Information - Setijanto, R. Darmawan; Rachmawati, Rita Yuana; Kandar, Hayyin Sabila; Hartono, Dwicha Rahma Nuriska; Novitananda, Agtadila; Laksono, Revian Gigih; Thalia, Audina; Dias, Dennaya Listya; Adityasari, Rachma; Sativa, Naura Athiyyah; Fauzi, Ahmad (Faculty of Dental Medicine Universitas Airlangga, 2019)
Background: Two main influencing factors of dental and oral health in developing countries are attitude and behavior. A person's behavior is influenced by intentions, attitudes, subjective norms, perceived control. Attitudes and parental behaviors, especially mothers, have a significant effect on children's behaviors, especially in maintaining dental health. A mother should be literate about and set examples on dental and oral health to her child. An epidemiological study conducted at the Kalijudan Health Center involving 105 research respondents reported that parental behavior, especiallyperceived control, had a significant effect on the dental health care of children under five. Therefore, we created an empowerment program by using WhatsApp as the communication platform. Dentists of Kalijudan Public Health Center (Puskesmas), cadres of Integrated Health Service Post (Posyandu), and mothers of children under five have joined the group to facilitate QA with the dentist regarding dental health care for children. Purpose: To ease the access to information and consultation regarding dental health care for children under five. Methods: To empower the mothers by having discussions with the stakeholders Kalijudan Public Health Center via WhatsApp group. Results: 5 out of 10 active mothers gave questions about the health of toddlers' teeth and were answered directly by a dentist representative from the Kalijudan Health Center during a two-hour forum. Conclusion: Cadres and mothers of children under five wereable to access information and consult with dentists of Kalijudan Public Health Center easily via WhatsApp group named SARASEHAN. The program was beneficial for mothers as it facilitated the mothers to learn more about their children's dental care.